Analisis Penanda dan Petanda dalam Kumpulan Puisi Tanah Laut Separuh Nafasku Karya Ida Komalasari - Riswandi, Muhammad; Hidayah, Hidayatul; Harpriyanti, Haswinda (UIR Press, 2026)
Poetry as a literary work is a form of linguistic expression that is rich in signs which construct meaning and represent human experiences and life reflections. This study employs a qualitative method using Ferdinand de Saussure’s semiotic approach, focusing on the relationship between signifier and signified in poetry. The research data are obtained from four poems in the poetry collection Tanah Laut Separuh Nafasku by Ida Komalasari. Data collection is conducted through close reading and note-taking techniques on words, phrases, and poetic lines containing signifier and signified elements. Data analysis is carried out by identifying signifiers and signifieds and interpreting their relationships to reveal the meanings constructed in the poems. The findings indicate that the distinctive characteristic of Ida Komalasari’s poetry lies in the use of signifiers derived from bodily experiences, time, and human biological conditions to form signifieds that represent existential reflections on mortality, loneliness, and human limitations. The relationship between signifier and signified produces contemplative and personal meanings, distinguishing Ida Komalasari’s poems from abstract tendencies in existential poetry.